Coming Back to the Basics. Comment on Cangir et al. A CT-Based Radiomic Signature for the Differentiation of Pulmonary Hamartomas from Carcinoid Tumors. Diagnostics 2022, 12, 416 - Armando Perrella; Giulio Bagnacci; Nunzia Di Meglio; Vito Di Martino; Cristiana Bellan; Luca Luzzi; Maria Antonietta Mazzei; Luca Volterrani (Diagnostics, 2023)
We read with great interest the article by Cangir et al., “A CT-Based Radiomic Signature for the Differentiation of Pulmonary Hamartomas from Carcinoid Tumors”, published on 5 February 2022 [...]